2019
DOI: 10.1002/ange.201901309
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐katalysierte Anellierung von Benzoesäuren mit α,β‐ungesättigten Ketonen durch C‐H‐, CO‐OH‐ und C‐C‐ Bindungsspaltung

Abstract: In Gegenwart eines [Cp*RhCl 2 ] 2 -Katalysators,d er Lewis-Säure In(OTf) 3 und der milden Base Na 2 CO 3 ,d urchlaufen aromatische Carboxylate und a,b-ungesättigte Ketone einen einzigartigen Hydroarylierungs/Claisen/retro-Claisen-Prozess um die entsprechenden Indanone zu bilden. Während dieser Carboxylat-dirigierten ortho-C-H-Anellierung wird sowohldie C-COR-Bindung des Ketons,als auch die CO-OH-Gruppe der aromatischen Carbonsäure,g espalten und die Hydroxylgruppe vom aromatischen Acylrest auf den aliphatische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Therefore, many organic chemists devote themselves to developing various strategies for this kind of reactions, especially the aerobic cleavage of C(CO)‐C bond that is used to produce acids, aldehydes, α ‐ketoesters, esters, amides, α‐ketoamides and β ‐ketophosphine oxides . Transition metals are generally considered as the catalyst to enable the aerobic oxidative C(CO)‐C bond cleavage . For example, several copper‐based catalyst systems such as CuI, pyridine/CuBr/BF 3 ⋅Et 2 O and Cu(NO 3 ) 2 ⋅3H 2 O were respectively demonstrated to be effective in the aerobic oxidative C(CO)–C cleavage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many organic chemists devote themselves to developing various strategies for this kind of reactions, especially the aerobic cleavage of C(CO)‐C bond that is used to produce acids, aldehydes, α ‐ketoesters, esters, amides, α‐ketoamides and β ‐ketophosphine oxides . Transition metals are generally considered as the catalyst to enable the aerobic oxidative C(CO)‐C bond cleavage . For example, several copper‐based catalyst systems such as CuI, pyridine/CuBr/BF 3 ⋅Et 2 O and Cu(NO 3 ) 2 ⋅3H 2 O were respectively demonstrated to be effective in the aerobic oxidative C(CO)–C cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Transition metals are generally considered as the catalyst to enable the aerobic oxidative C (CO)-C bond cleavage. [10] For example, several copper-based catalyst systems such as CuI, [11] pyridine/CuBr/BF 3 ⋅Et 2 O [12] and Cu(NO 3 ) 2 ⋅3H 2 O [13] were respectively demonstrated to be effective in the aerobic oxidative C(CO)-C cleavage. It has been reported that FeCl 3 has the ability to catalyze this transformation (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%